"From analog to digital": The feasibility, acceptability, and preliminary outcomes of a positive parenting program for street-connected mothers in Kenya. (August 2021) - Murphy, Kathleen; Embleton, Lonnie; Lachman, Jamie M.; Owino, Eucabeth; Kirwa, Sheila; Makori, Dominic; Braitstein, Paula
Highlights: This is the first known study of a positive parenting program for street-connected parents in Kenya. The adapted program is both feasible and acceptable with this population. This program may reduce the use of corporal punishment among street-connected parents. The program may increase positive parenting practices within this population. The program may reduce parental stress. Abstract: Background: Children of street-connected women in Kenya are at risk of child maltreatment. There have been increasing calls for positive parenting programs for parents experiencing homelessness, however never has one been implemented with this population. We therefore adapted the evidence-based Parenting for Lifelong Health for Young Children program using participatory methods, and piloted the adapted program with street-connected mothers in Kenya. Objectives: To (a) determine if the adapted program was feasible and acceptable with street-connected mothers, and (b) assess indicative effects on child maltreatment, positive parenting, and parental stress. Participants and setting: Two groups of 15 mothers (ages 19+, and 20−) participated between June-July 2018 in Eldoret, Kenya. Participants were eligible if they (a) were the mother of at least one child and (b) self-identified as street-connected. Methods: Feasibility was measured via enrollment, attendance, drop-out rates, and engagement in take-away activities. Focus groups explored program acceptability and program outcomes. Self-report surveys assessed pre-post changes in child maltreatment, parental stress, parental sense of inefficacy, and positive parenting practices. Results: 70% of participants attended >3/4 of sessions, 10% dropped out, and >50% of take-away activities were completed. Participants reported high acceptability and requested its continuation for themselves and other parents. There was an increase in supporting good behaviour (t(21) = 8.15, p < .000) and setting limits (t(18) = 10.03, p < .000); a reduction in physical abuse (t(23) = −2.15, p = .042) and parental stress (t(22) = −7.08, p < .000); results for parental inefficacy were not statistically significant (t(22) = 0.15, p = .882). Conclusions: The adapted program is feasible and acceptable to street-connected mothers, and may reduce child maltreatment and parental stress, and increase positive parenting. Further research should test program effectiveness.